Pengembangan Pendekatan Somatic – Auditory – Visualization Intellectually (SAVI) Dalam Meningkatkan Kemampuan Pemecahan Masalah Pada Mata Pelajaran Fikih Melalui Pembelajaran Jarak Jauh; Studi Di MTs Nidhomiyah Surowono Kecamatan Badas Kabupaten Kediri - Haizatul Masnaiyah; Sri Susanti Tjahja Dini (Institut Agama Islam Tribakti Kediri, 2020)
The outbreak of the coronavirus disease (Covid 19) in Indonesia has prompted the Ministry of Education and Culture and the Ministry of Religion to urge schools to organize distance learning. Because of this appeal, schools and madrasas organize distance learning activities, including MTs Nidhomiyah Surowono, Badas District. However, the distance learning of fiqh subjects is only providing assignments through the WA group and there is no feedback from the teacher. This phenomenon causes the problems solving skills of the students to become low. So research and development (R & D) were done on the fiqh subjects to describe 1) the steps for developing somatic-auditory-visualization-intellectually (SAVI) approach through distance learning, and 2) the effectiveness of developing somatic-auditory-visualization-intellectually approach (SAVI) to increase the problem-solving skills on the fiqh subjects through distance learning. This research used the research and development (R & D) approach Borg and Gall model that combined with the ADDIE model. The testing model used an experimental pretest-posttest control group design. The result of the pretest and posttest were analyzed by the test of normality, homogeneity, N-gain scores, and independent-sample t-test with IBM SPSS Statistics version 21. The results showed that the SAVI approach was quite effective in improving students' problem-solving skills. This can be seen based on the results of the pre-test and post-test in the experimental class compared to the control class. From the experimental class, it was obtained that the pre-test results had an average of 52, but after receiving the SAVI approach, the post-test score was 67. Far different from the control class whose initial class average score was 49 to 56. This is also supported by the mean results of the N-gain score for the experimental class was 33.5513 or 33.6 which was included in the moderate or moderately effective criteria. [Merebaknya infeksi virus Covid 19 di Indonesia membuat Mendikbud dan Kemenag menghimbau sekolah-sekolah untuk melaksanakan pembelajaran secara jarak jauh. Atas himbauan tersebut, sekolah dan madrasah melakukan kegiatan pembelajaran jarak jauh, termasuk MTs Nidhomiyah Surowono Kecamatan Badas. Namun, pembelajaran yang dilakukan pada mata pelajaran fikih hanya sebatas pemberian tugas melalui grup WA dan tidak ada umpan balik dari guru. Hal tersebut mengakibatkan rendahnya kemampuan pemecahan masalah yang dikuasai peserta didik. Maka dilakukanlah penelitian dan pengembangan (R & D) pada mapel fikih dengan tujuan untuk mendeskripsikan 1) langkah-langkah pengembangan pendekatan somatis-auditory-visualization-intellectually (SAVI) melalui pembelajaran jarak jauh, dan 2) efektivitas pengembangan pendekatan somatis-auditory-visualization-intellectually (SAVI) dalam meningkatkan kemampuan pemecahan masalah fikih melalui pembelajaran jarak jauh. Penelitian dan pengembangan (R & D) yang digunakan dalam penelitian ini adalah model Borg and Gall yang kombinasikan dengan model ADDIE. Uji coba model dalam penelitian ini menggunakan bentuk desain eksperimen pretest-posttest control group desain. Data pretest dan posttest yang diperoleh dianalisis dengan uji normalitas, homogenitas, Ngain score dan uji independet sampel t tes dengan bantuan aplikasi IBM SPSS Statistics versi 21. Hasil penelitian menunjukkan pendekatan SAVI cukup efektif dalam meningkatkan kemampuan pemecahan masalah yang dikuasai siswa. Hal ini dapat dilihat berdasarkan hasil dari pre test dan pos test pada kelas eksperimen yang dibandingkan dengan kelas kontrol. Dari kelas eksperimen diperoleh hasil pre test memiliki rata-rata 52 namun setelah mendapat perlakuan pendekatan SAVI diperoleh nilai post test 67. Jauh berbeda dengan kelas kontrol yang nilai rata-rata kelas yang awalnya adalah 49 menjadi 56. Hal ini didukung pula dengan hasil rata-rata N-gain score kelas eksperimen sebesar 33,5513 atau 33,6 yang masuk dalam kriteria sedang atau cukup efektif]